Multifunctional plant growth promoting potential of Burkholderia vietnamiensis-OP984178 and B. ambifaria-OP984173 isolated from rhizosphere soils, Tanzania - Grace MPINDA; Nyambilila AMURI; Hamis TINDWA (Journal of Central European Agriculture, 2024)
This study aimed to isolate and identify phosphate solubilizing microorganisms from rhizosphere soils and evaluate their plant growth-promoting traits in vitro. Fifty-six potential phosphate-solubilizing bacteria were isolated, and ten isolates were selected for further characterization based on their performance. Burkholderia species were found to be the predominant solubilizers of insoluble phosphorus sources. Two strains, B. vietnamiensis-OP984178 and B. ambifaria-OP984173, showed the ability to release soluble phosphorus from different sources, including tricalcium phosphate, ferric phosphate, and hard Minjingu rock phosphate powder. Both isolates also demonstrated production of indole acetic acid, with B. vietnamiensis-OP984178 and B. ambifaria-OP984173 producing up to 23.45 μg/ml and 24.24 μg/ml, respectively. Furthermore, the strains showed antifungal efficiencies of 31.48% and 24.81%, respectively, when co-inoculated with Fusarium proliferatum-MZ497514 on potato dextrose agar. The study also identified the nitrogen fixation potential of the two strains. Overall, the findings highlight the potential of the selected Burkholderia strains as biofertilizers and biocontrol agents, making them valuable candidates for sustainable agriculture practices. Further research is recommended to explore the potential of these strains using test crops.